Simultaneous identification of low and high atomic number atoms in monolayer 2D materials using 4D scanning transmission electron microscopy - Wen, Y; Ophus, C; Allen, CS; Fang, S; Chen, J; Kaxiras, E; Kirkland, AI; Warner, JH (American Chemical Society, 2019)
Simultaneous imaging of individual low and high atomic number atoms using annular dark field scanning transmission electron microscopy (ADF-STEM) is often challenging due to substantial differences in their scattering cross sections. This often leads to contrast from only the high atomic number species when imaged using ADF-STEM such as the Mo and 2S sites in monolayer MoS2 crystals, without detection of lighter atoms such as C, O, or N. Here, we show that by capturing an array of convergent beam electron diffraction patterns using a 2D pixelated electron detector (2D-PED) in a 4D STEM geometry enables identification of individual low and high atomic number atoms in 2D materials by multicomponent imaging. We have used ptychographic phase reconstructions, combined with angular dependent ADF-STEM reconstructions, to image light elements at lateral (nanopores) and vertical interfaces (surface dopants) within 2D monolayer MoS2. Differential phase contrast imaging (Div(DPC)) using quadrant segmentation of the 2D pixelated direct electron detector data not only qualitatively matches the ptychographic phase reconstructions in both resolution and contrast but also offers the additional potential for real time display. Using 4D-STEM, we have identified surface adatoms on MoS2 monolayers and have separated atomic columns with similar total atomic number into their relative combinations of low and high atomic number elements. These results demonstrate the rich information present in the data obtained during 4D-STEM imaging of ultrathin 2D materials and the ability of this approach to extract unique insights beyond conventional imaging.